HOLISTIC DEVELOPMENT OF STUDENTS IN SCHOOLS: LIFE SKILLS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Life skill education is the process of gaining and developing the sets of abilities that allow people to successfully manage the different challenges and demands of everyday life. These skills and comparability of a wide variety of competences, including personal, social, emotional, and cognitive abilities, as well as practical skills that are required for independent life in well-being Life skill education aims to empower individuals for decision making, problem solving, communication skill, management skills, etc. According to National Educational Policy (NEP 2020), life skill education is the integration into the curriculum to ensure holistic development of learners and recognize the importance of developing skills such as critical thinking, creativity, communication, and collaboration with academic learning (Ministry of Education, Government of India, 2020) and also promotes positive outcomes in domains like academic achievement, mental health and social competence.